The Extended Center of Groups - As’ad Y. As’ad (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In this paper we define and study a new concept called the extended center of a group. Some examples are given and some results are obtained to explain some of the properties of the extended center of a group. Finally, homomorphism and extended center of groups are studied.